Determining the Value of an Orchard Tree - Edward Evans; Carlos Balerdi; Jonathan Crane; Sikavas Nalampang (EDIS, 2006)
FE676, a 4-page illustrated fact sheet by Edward Evans, Carlos Balerdi, Jonathan Crane, and Sikavas Nalampang, provides step-by-step instructions for using the agecon-trec software program to estimate the value of a tree that has been destroyed. Published by the UF Department of Food and Resource Economics, November 2006.